Optimalisasi Alokasi Biaya Langsung dan Tidak Langsung untuk Peningkatan Kualitas Layanan Pendidikan - Iffatul Aimmah (Journal of Public Policy Analys, 2024)
Education costs, which are divided into direct costs and indirect costs, play an important role in improving the quality of education services. An appropriate allocation strategy for these two types of costs is urgently needed to optimize the sustainability of educational operations. This study aims to find out strategies and challenges in optimizing the allocation of education costs to improve education services. The method used in this study is library research. The results of this study show that several strategic steps include direct cost allocation for infrastructure, development of the quality of educators through training, technology procurement, strengthening extracurricular activities for soft skills, and regular evaluation of budget allocation. However, there are challenges in optimizing cost allocation, such as budget limitations, imbalances in fund allocation, lack of transparency, lack of technological support, and social and economic inequality.